Studies on the basic building blocks of light-harvesting complexes using ultrafast two-dimensional electronic spectroscopy - Muhammad Faisal Bin Khyasudeen (2019)
This dissertation describes the development of ultrafast two-dimensional electronic spectroscopy (2DES) using pump-probe geometry and its application in interrogating the underlying femtosecond to picosecond dynamics of basic building blocks in plant light- harvesting complexes (LHC). In the second chapter of this thesis, we provide the description and development of 2DES using a partially collinear geometry. The procedure for post analysis such as conversion of raw data into a purely absorptive 2D data was included in this part of the thesis. The application of 2DES is divided here into three main chapter. In chapter 3, we aims to investigate the effect of finite bandwidth of the interaction pulses in retrieval of the FFCF from 2D spectrum using three different methods (CLSω1, CLSω3, ellipticity). Although all of the methods show correct values in broad excitation bandwidth, our results show that it does not hold true when the excitation bandwidth becomes narrower than the studied absorption band. We used Chl a molecules to test and show that with the help of simulation of the 2D spectra, it is possible to recover the FFCF using any of these methods. Chl a and Chl b are major constituent pigments in LHC complexes. The primary roles of Chl molecules is to absorb light and transfer the energy on a sub-picosecond timescale to the reaction center for the light-chemical energy conversion. It is well established that proteins surrounding Chl molecules play a significant role in optimizing this process. Therefore, understanding the effect of local environment on Chls electronic transition is an important subject to study. 2DES provides a remarkably sensitive tool to study the solute-solvent interaction with high spectral and time resolution. Accompanied by the center line slope (CLS) analysis, in chapter 4, we elucidate the spectral diffusion dynamics of Chlorophyll a (Chl a) and Chlorophyll b (Chl b) in various chemical environments. 2DES was used to measure the frequency fluctuation correlation function (FFCF) of Chl a and Chl b electronic transition. Three time scales and amplitudes of the frequency fluctuations were recovered for the lowest excited state of Chl ranging from hundreds of femtoseconds to picosecond timescales and assigned as the solvation dynamics and spectral diffusion. By measuring them in various solvents, our results revealed significant differences in the extent of inhomogeneous broadening depending on the solvent used, with the biggest contribution of inhomogeneous broadening being due to the polar hydrogen bond solvent and smallest due to the nonpolar solvents. Interestingly, by comparing the results between Chl a and Chl b, our measurements indicated an effect of substituent group in porphyrin ring at position 7 on the rate of relaxation dynamics from an initially inhomogeneous broadening becoming more homogeneous at later Tw (population time). Such evolution was found to be faster for Chl a than Chl b as described in the chapter 4 of this thesis. In the last part of this study (Chapter 5), we utilized 2DES to observe the mechanism of population transfer from the Qx band (S2 state) to the Qy band (S1 state) in Chl a molecule. An ultrafast relaxation from Qx to Qy band was observed to take place in less than Tw=150 fs. Furthermore, observing the cross peak after excitation of the Qx band reveals the type of correlation between the two transition dipole moments. Our results indicate that the Qx and Qy band exhibit minimal correlation even at very short population times. We suggest a possible mechanism explaining lack of the correlation that is based on the fact that the Qx and Qy transition dipole moments are orthogonally oriented with respect to each other.